Fundamental of Entrepreneurship (ENT300) : Uncle Bun Enterprise / Norazlina Abd Halim - Abd Halim, Norazlina (2020)
UNCLE BUN ENTERPRISE is the bread shop that establish in Jitra, Kedah. We offer the product and service for the customer who wanted to eat the bread as the food in the breakfast,lunch and supper. In the simple word, it suitable for every times. We provide the variety of the bread to our customer. We want to make sure the customer who purchase our bread will be satisfy and will be the repeat of our product. We will make sure all bread made every day.